(untitled) (Annals of Medical Research, 2021)
Aim: Patients with Fabry disease frequently die due to cardiovascular causes. There are numerous findings of cardiovascular involvement in patients with Fabry disease. Epicardial fat thickness is a surrogate for various cardiovascular diseases. In this study, we evaluated epicardial fat thickness and parameters of diastolic dysfunction among Fabry patients as a possible indicator of disease severity.Materials and Methods: We enrolled 14 patients with Fabry disease who receive enzyme replacement therapy. Detailed echocardiographic examination was performed including diastolic functions and measurement of epicardial fat thickness. Disease severity was assessed using DS3 scoring system. Based on DS3 scores, patients are grouped into mild (10 points), moderate (10-28 points) and severe (29-32 points) disease.Results: There were two female and twelve male patients with Fabry disease. Patients were classified into three groups based on DS3 scores. Epicardial fat thickness was significantly increased among patients with advanced disease compared to patients with mild disease (p:0.002). Also, epicardial fat thickness had significant positive correlation with average E/E’ ratio (p:0.014), left atrial volume (p:0.004) and left atrial volume index (p:0.022).Conclusion: Epicardial fat thickness seems as a promising new marker of disease severity among patients with Fabry disease.Keywords: Fabry’s disease; inflammation; echocardiography.